HOW DOES SELFSACRIFICIAL LEADERSHIP AFFECT KNOWLEDGE SHARING AND KNOWLEDGE HIDING?: THE MEDIATING EFFECTS OF EMPLOYEES’ TRUST AND INTRINSIC MOTIVATION - R. Sabrina (The Journal of Modern Project Management, 2023)
The present study is based on Social-Exchange Theory and examines the relationship between self-sacrificial leadership and employees’ knowledge-sharing and knowledge-hiding behaviors. This study represents an advancement in the field by building upon previous research. Additionally, scholarly research has examined the mediatory role psychological safety and perceived supervisor support. A longitudinal field survey was conducted to gather data from 452 employees employed at various levels within small and medium enterprises in Medan, Indonesia. The findings indicate a positive and significant correlation between self-sacrificial leadership and employees’ Knowledge sharing behavior. It has been observed that an adverse correlation exists between self-sacrificial leadership and the tendency of employees to conceal their knowledge. Additionally, the findings indicate a relationship between self-sacrificial leadership and employees’ knowledge-sharing and knowledge-hiding behaviors, which are influenced by psychological safety and perceived supervisor support. The statement mentioned above illustrates a process of exchange whereby the endeavors of self-sacrificing leaders are transformed into the establishment of safety among employees, thereby fostering perception of supervisor support to share Knowledge amongst peers while simultaneously discouraging the concealment of Knowledge. Moreover, the present investigation has contributed to the existing literature on the consequences of self-sacrificial leadership. It has also delved into the underlying mechanisms that facilitate such outcomes, particularly in the setting of small and medium-sized enterprises (SMEs) in Indonesia. The paper concludes by proposing key policy insights, theoretical implications, practical implications, and future research directions.